2006
DOI: 10.1007/s10530-004-2310-2
|View full text |Cite
|
Sign up to set email alerts
|

Popularity and Propagule Pressure: Determinants of Introduction and Establishment of Aquarium Fish

Abstract: Propagule pressure is frequently cited as an important determinant of invasion success for terrestrial taxa, but its importance for aquatic species is unclear. Using data on aquarium fishes in stores and historical records of fish introduced and established in Canadian and United States waters, we show clear relationships exist between frequency of occurrence in shops and likelihood of introduction and of establishment. Introduced and established taxa are also typically larger than those available from stores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
171
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(200 citation statements)
references
References 13 publications
7
171
0
9
Order By: Relevance
“…Despite the revenues and jobs generated by the aquarium/ornamental fish trade (reviewed in Tlusty, 2002), it has been identified as a major driver for nonnative fish introductions into the wild, particularly for the freshwater species (Copp et al, 2005;Duggan et al, 2006;Corfield et al, 2008). Also, in the USA, 26% of human-mediated alien fish diversity was attributed to the aquarium trade (Fuller et al, 1999) and 115 freshwater aquarium species have been reported as introduced into the wild (Padilla & Williams, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the revenues and jobs generated by the aquarium/ornamental fish trade (reviewed in Tlusty, 2002), it has been identified as a major driver for nonnative fish introductions into the wild, particularly for the freshwater species (Copp et al, 2005;Duggan et al, 2006;Corfield et al, 2008). Also, in the USA, 26% of human-mediated alien fish diversity was attributed to the aquarium trade (Fuller et al, 1999) and 115 freshwater aquarium species have been reported as introduced into the wild (Padilla & Williams, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Propagule pressure of NICS is recognized as one of the main factors of establishment (Capinha et al, 2013). Consequently, the quantity of NICS in the pet trade is directly correlated with the probability of their release into the wild and their possible establishment similarly to fish released from aquaria (Duggan et al, 2006). Although a risk assessment for ornamental NICS in the Czech Republic (Patoka et al, 2014a) and an analysis of keeper behaviour (Patoka et al, 2014b) have been published, detailed information focused on the origin of imported ornamental crayfish and their prices and quantities 04p2…”
Section: Introductionmentioning
confidence: 99%
“…Fishkeeping is increasing in popularity, but hobbyists are poorly informed or reckless about environmentally friendly practices (Duggan et al, 2006;Gertzen et al, 2008;Holmberg et al, 2015;Maceda-Veiga et al, 2016). For example, excessive growth and unexpected aggressive behavior of fishes may lead to environmental problems, i.e, aquarium dumping (Duggan et al, 2006;Gertzen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, excessive growth and unexpected aggressive behavior of fishes may lead to environmental problems, i.e, aquarium dumping (Duggan et al, 2006;Gertzen et al, 2008). Under these circumstances, many hobbyists are poorly informed about adequate practices (i.e, correct disposal of pets or even sacrifice), and discard unwanted pets into nearby waterways (Duggan et al, 2006;Gertzen et al, 2008;Magalhães, Jacobi, 2013a;Azevedo-Santos et al, 2015;Maceda-Veiga et al, 2016). Pet abandonment has become one of the most challenging issues in biosecurity concerning species invasions (CBD, 2010).…”
Section: Introductionmentioning
confidence: 99%